2021
DOI: 10.21037/qims-20-895
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study for ex vivo fluorescence confocal microscopy (FCM) on diagnostic prostate biopsies

Abstract: Background: Fluorescence confocal microscopy (FCM) is a novel micro-imaging technique providing optical sections of examined tissue. The method has been well established for the diagnosis of tumours in dermatological specimens. Preliminary results found good feasibility when this technique was used to examine prostate cancer (PCa) specimens.Methods: We report on the application of FCM in magnet resonance imaging (MRI)-fused prostate biopsies (10 patients, total number of biopsy specimens: n=121) and compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…This is explained by the low penetration depth of AO at an incubation time of 30 s which we found in our previous examinations of biopsy material. We previously demonstrated that DNA content was not significantly diminished after pre-treatment for FCM [32]. Therefore, any necessary immuno-histological or even molecular examinations of diagnostically difficult tumors do not constitute an obstacle to preliminary examinations in FCM.…”
Section: Discussionmentioning
confidence: 96%
“…This is explained by the low penetration depth of AO at an incubation time of 30 s which we found in our previous examinations of biopsy material. We previously demonstrated that DNA content was not significantly diminished after pre-treatment for FCM [32]. Therefore, any necessary immuno-histological or even molecular examinations of diagnostically difficult tumors do not constitute an obstacle to preliminary examinations in FCM.…”
Section: Discussionmentioning
confidence: 96%
“…This material-sparing method conserves the biopsies as unfixed material for further histological, immunohistological, and even molecular analysis. In our preliminary examinations, we found that the pre-treatment for FCM did not alter the feasibility of the material for further FISH examinations and extraction of DNA [26].…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies have shown that prostate carcinoma can be reliably detected and diagnosed with FCM in good agreement with final histology [21][22][23]. The specimens remain as unfixed tissue without loss and are available for subsequent histological, immunohistological and molecular examinations [24].…”
Section: Introductionmentioning
confidence: 69%